1989
DOI: 10.1093/nar/17.14.5489
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of human cDNA clones ofskiand the ski-related gene,sno

Abstract: cDNA clones of ski and the ski-related gene, sno, were obtained by screening human cDNA libraries. The predicted open reading frame of h-ski could encode a protein of 728 amino acid residues. The h-ski protein is highly homologous with the v-ski protein. The overall homology between h-ski and v-ski is 91% at the amino acid level. DNA sequencing analysis revealed two types of cDNA clones from the sno (ski-related novel gene) gene, possibly due to alternative splicing. The first type, named snoN (non Alu-contain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
210
0

Year Published

1994
1994
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 167 publications
(216 citation statements)
references
References 45 publications
6
210
0
Order By: Relevance
“…Overexpression of c-Ski abolished TGF-␤-induced growth inhibition (Luo et al, 1999;Sun et al, 1999;Xu et al, 2000). High levels of expression of c-Ski were reported in several tumor cell lines (Nomura et al, 1989;Fumagalli et al, 1993) and in melanomas in vivo (Reed et al, 2001). Inhibition of TGF-␤ signaling is thus regarded as a part of the mechanism of oncogenesis by Ski proteins (He et al, 2003).…”
Section: Introductionmentioning
confidence: 98%
“…Overexpression of c-Ski abolished TGF-␤-induced growth inhibition (Luo et al, 1999;Sun et al, 1999;Xu et al, 2000). High levels of expression of c-Ski were reported in several tumor cell lines (Nomura et al, 1989;Fumagalli et al, 1993) and in melanomas in vivo (Reed et al, 2001). Inhibition of TGF-␤ signaling is thus regarded as a part of the mechanism of oncogenesis by Ski proteins (He et al, 2003).…”
Section: Introductionmentioning
confidence: 98%
“…High levels of Ski or SnoN are associated with many types of human cancer cells. 7,8 Ski or SnoN antagonize TGF-b signaling through direct interaction with Smad4, Smad2 or Smad3. [9][10][11][12] A 8-bp palindromic sequence (GTCTAGAC) was initially identified to be a high-affinity binding site for Ski.…”
mentioning
confidence: 99%
“…Previous reports have demonstrated that ski is ubiquitously expressed at low levels (Colmenares and Stavnezer, 1990;Nomura et al, 1989). Reverse transcriptase PCR analysis detected skip expression in all cell lines that were tested (data not shown).…”
Section: Discussionmentioning
confidence: 62%
“…V-Ski is truncated at the amino and carboxyl termini compared to the cellular proto-oncogene c-Ski. Ski has been cloned from several species including human, chicken, and Xenopus (Nomura et al, 1989;Sleeman and Laskey, 1993;Sutrave et al, 1990a); and is the founding member of a family of proteins which includes itself and the Ski related protein Sno (Boyer et al, 1993).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation